An evaluation of Lycosa hilaris as a bioindicator of organophosphate insecticide contamination - Hodge, S.; Vink, C.J. (New Zealand Plant Protection, 2000)
The potential of Lycosa hilaris as a bioindicator of organophosphate contamination was assessed experimentally in a crop of beans (Phaseolus vulgaris) in Canterbury New Zealand Although the numbers of L hilaris caught in pitfall traps fluctuated significantly as the crop aged there were no differences (P>005) in L hilaris abundance in plots sprayed with diazinon or chlorpyrifos compared with plots of beans sprayed with water The abundances of other beneficial arthropod predators (linyphiid spiders harvestmen centipedes) were also not affected by insecticide application (P>005) Although L hilaris may not represent a good bioindicator the use of this species as a laboratory bioassay organism should be further investigated especially with respect to sublethal physiological responses